A Double-Edged Sword? Legal Certainty and the Perils of Authority in Indonesia’s Draft Asset Deprivation Act - Hisbul Luthfi Ashsyarofi; Arfan Kaimuddin; R.B. Muhammad Zainal Abidin; Bastomi, Ahmad (Universitas Negeri Semarang, 2024)
The urgency of enacting the Draft Asset Deprivation Act in Indonesia stems from the need to recover assets linked to criminal activities, even in the absence of a conviction. This approach is seen as a preventive measure to safeguard illicitly acquired assets; however, its implementation raises serious legal concerns. The potential violation of property rights—recognized as fundamental human rights—poses risks to justice and legal certainty. The lack of clear procedural safeguards could lead to authority abuse, arbitrary asset seizures, and disproportionate impacts on individuals. This study identifies critical inconsistencies within the draft law. First, the phrase